Osteoporosis in children: pediatric and pediatric rheumatology perspective: a review - Uziel, Yosef (BioMed Central, 2009)
It is increasingly recognized that osteoporosis affects children as well as adults both as a primary problem and as secondary to various diseases, medications, and lifestyle issues. In this review, we emphasize the correct diagnosis of osteoporosis in children as opposed to adults, etiology, and pharmaceutical and non-pharmaceutical treatments. We especially focus on rheumatologic conditions associated with osteoporosis and management issues.